PROBLEMATIKA DALAM PENGIMPLEMENTASIAN KURIKULUM MERDEKA MATA PELAJARAN AL-QUR’AN DAN HADIS KELAS 10 DI MAN 2 SLEMAN YOGYAKARTA - Raisa Zuhra Salsabila Awaluddin; Muh. Wasith Achadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Textbooks that must be owned by educators to achieve learning achievements and have guidelines in teaching. The reality in the field, MAN 2 Sleman, especially the subject of Al-Qur'an Hadith, does not yet have a textbook. This problem is not a common thing that must be accepted by educators. Educators must find relevant books or take from the internet. This research uses a type of qualitative field research (Field Research). The data sources of this research used books and articles. The data collection technique uses observation, interviews and documentation. The data analysis technique uses data reduction, selecting key things, focusing on important things, looking for themes and patterns, presenting data, drawing conclusions. The results of this study are problems such as textbooks that have not been obtained. The readiness of educators in teaching that has not been applied in the subject of Al-Qur'an Hadith. Then, the use of variation methods that must be heeded when discussing in order to make it easier to capture lessons and not look monotonous. Furthermore, reading the Qur'an before the lesson is wrong for people with disabilities to practice tajweed. Making teaching modules is a problem for educators to prepare for learning. Then, tajweed material that does not exist in MAN becomes a problem when students are not from MTS. Therefore, there are many limitations in reading the Qur'an at MAN 2 Sleman.